An analysis of health tourism: The example of Kołobrzeg - Oleszczyk, Natalia; Dominiak, Natalia (Turyzm/Tourism, 2021)
In recent years, there has been a growing global interest in spa tourism, as well as a significant increase in social awareness of the need to care for health, physical fitness and well-being. Apart from spa tourism, ‘spa & wellness’ tourism is also very popular. Kołobrzeg, in addition to being a town largely geared towards patients, also attracts tourists who take advantage of ‘spa & wellness’ treatments. The purpose of this article is to define the essence and characteristics of spa tourism based on the example of Kołobrzeg. Spa activities are carried out in health care entities operating in the zone of the spa, places where patients are undergoing treatment or rehabilitation. These benefit from the healing natural conditions of the areas in which they operate and their microclimates. The main part of the article presents the history of spa tourism in Kołobrzeg along with an analysis of its spa offer and therapeutic profile. In addition, the empirical part discusses the results of an analysis among patients using the survey method; a large proportion of respondents were over 65, mainly female. During the study, the respondents rated various aspects of their spa stay (on a scale from 1 to 5) at a level above 4.0, which indicates the healthy condition of the spa itself and general satisfaction among patients.